THE ROLE OF SOCIAL OBSTACLES AND THEIR CAUSES IN AFFECTING STUDENTS' ACADEMIC ACHIEVEMENT AND METHODS OF TREATMENT IN THE UAE: STUDENTS OF THE THIRD CYCLE OF ZAYED THE FIRST SCHOOL – MODEL - Abdul Rahman, Asma; Almazroui, Karina; Abdul Rahman, Maryam (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
This study examines the impact of social obstacles on the academic achievement of third-cycle students in the United Arab Emirates (UAE) and proposes solutions to address these challenges. Using a social survey methodology, data were collected via a questionnaire at Zayed the First School in Abu Dhabi, involving 73 participants, including students, teachers, families, and staff. The study categorizes obstacles into cultural, familial, professional, and self-imposed barriers, highlighting key issues. This includes strained student-teacher relationships, bullying, excessive academic workloads, and extended study hours, negatively impacting students' academic and social development. Additionally, the lack of cultural awareness among some expatriate teachers and family challenges, including neglect, overprotection, or disintegration, undermined students' self-confidence and engagement. The study emphasizes the need for a holistic educational framework that prioritizes students' emotional and social well-being alongside academic growth. Schools must function as socio-educational institutions, fostering collaboration between families and educators to create a supportive and culturally sensitive environment. Open communication is critical for addressing challenges, reinforcing positive behaviors, and ensuring alignment in supporting students. The findings advocate for strategic interventions to enhance social cohesion, emotional support, and cultural understanding, enabling students to thrive academically and socially within a nurturing educational ecosystem.